Sequential one-pot synthesis of bis(indolyl)glyoxylamides: Evaluation of antibacterial and anticancer activities. Issue 13 (1st July 2016) - Tantak, Mukund P.; Gupta, Vishakha; Nikhil, Kumar; Arun, V.; Singh, Rajnish Prakash; Jha, Prabhat Nath; Shah, Kavita; Kumar, Dalip
Graphical abstract: Abstract: A series of bis(indolyl)glyoxylamides10a –n has been designed and synthesized. In situ generated indole-3-glyoxalylchloride from the reaction of readily available indole9 with oxalyl chloride was treated with tryptamine to produce bis(indolyl)glyoxylamides10a –n in 82–93% yields. All the synthesized bis(indolyl)glyoxylamides were well characterized and tested for their antibacterial activity against Gram-positive and Gram-negative bacterial strains. Compounds10d, 10g and10i were found to display potent antibacterial activity against Gram-negative strain. Further, the cytotoxicity of bis(indolyl)glyoxylamides10a –n were evaluated against a panel of human cancer cell lines. Of the screened analogues, compound10f (IC50  = 22.34 μM; HeLa, 24.05 μM; PC-3, 21.13 μM; MDA-MB-231 and 29.94 μM; BxPC-3) was identified as the most potent analogue of the series. Exposure of PC-3 cells to either10a or10f resulted in increased levels of cleaved PARP1, indicating that bis(indolyl)glyoxylamides induce apoptosis in PC-3 cells. Most importantly, compounds10d, 10g and10i were completely ineffective in mammalian cells, suggesting that they target bacterial-specific targets and thus will not display any toxicity in host cells.